Comb Poly(Oligo(2‐Ethyl‐2‐Oxazoline)Methacrylate)‐Peptide Conjugates Prepared by Aqueous Cu(0)‐Mediated Polymerization and Reductive Amination. Issue 2 (17th November 2016) - Collins, Jennifer; Wallis, Sacha J.; Simula, Alexandre; Whittaker, Michael R.; McIntosh, Michelle P.; Wilson, Paul; Davis, Thomas P.; Haddleton, David M.; Kempe, Kristian
Abstract : The controlled synthesis of poly(oligo(2‐ethyl‐2‐oxazoline)methacrylate) (P(OEtOxMA)) polymers by Cu(0)‐mediated polymerization in water/methanol mixtures is reported. Utilizing an acetal protected aldehyde initiator for the polymerization, well‐defined polymers are synthesized (>99% conversion, Ð < 1.25) with subsequent postpolymerization deprotection resulting in α‐aldehyde end group containing comb polymers. These P(OEtOxMA) are subsequently site‐specifically conjugated, via reductive amination, to a dipeptide (NH2 ‐Gly‐Tyr‐COOH) as a model peptide, prior to conjugation to the functional peptide oxytocin. The resulting oxytocin conjugates are evaluated in comparison to poly(oligo(ethylene glycol) methyl ether methacrylate) combs synthesized in the same manner for potential effects on thermal stability in comparison to the native peptide. Abstract : The controlled Cu(0)‐mediated polymerization of OEtOxMA is reported in water/alcohol mixtures. The facile incorporation of α‐end functionality capable of undergoing postpolymerization peptide conjugation leads to well‐defined peptide–polymer conjugates.